The hidden opportunity cost of time effect on intertemporal choice - Zhao, Cui-Xia; Jiang, Cheng-Ming; Zhou, Lei; Li, Shu; Rao, Li-Lin; Zheng, Rui (Frontiers in Psychology, 2015)
An interesting phenomenon called “hidden opportunity cost of time effect” was detected in intertemporal choices. The majority of our participants preferred the smaller but sooner (SS) option to the larger but later (LL) option if opportunity cost was explicit. However, a higher proportion of participants preferred the LL to SS option if opportunity cost was hidden. This shift violates the invariance principle and opens a new way to encourage future-oriented behavior. By simply mentioning the ‘obvious’ opportunity cost of alternatives, decision makers can be more informed in prioritizing their long-term goals rather than short-term goals.